Nutritional strategies in abdominal surgery: the potential of ketogenic diet - Xu, Longjie; Li, Xiaohua; Cao, Chun (Frontiers in Nutrition, 2026)
Metabolic stress responses in the perioperative period of abdominal surgery can lead to systemic inflammatory response syndrome and accelerate the breakdown of glycogen, lipids and proteins, which affect skeletal muscle content and have a negative impact on patient functional recovery. Comprehensive perioperative nutritional support can improve patients' preoperative physical state and reduce postoperative complications. The ketogenic diet (KD), which consists of low carbohydrate, moderate protein and high fat contents, is widely used for the treatment of obesity and neurodegenerative diseases, and recent studies have focused on the associations between KD and perioperative nutritional support for abdominal surgery. In this review, the concept of KD and its metabolic mechanisms, as well as the potential benefits of KD during the perioperative period of abdominal surgery, are discussed. In addition, the risks and challenges of KD and the corresponding solutions are presented as well. A comprehensive understanding of the mechanisms by which KD acts may provide new nutritional strategies to improve the prognosis of abdominal surgery patients.